Consequences of Extracellular Matrix Remodeling in Headway and Metastasis of Cancer along with Novel Immunotherapies: A Great Promise for Future Endeavor - Ray, Suman K.; Mukherjee, Sukhes (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Tissues are progressively molded by bidirectional correspondence between denizen cells and extracellular matrix (ECM) via cell-matrix connections along with ECM remodeling. The composition and association of ECM are spatiotemporally directed to control cell conduct and differentiation; however, dysregulation of ECM dynamics prompts the development of diseases, for example, cancer. Emerging information demonstrates that hypoxia may have decisive roles in metastasis. In addition, the sprawling nature of neoplastic cells and chaotic angiogenesis are increasingly influencing microcirculation as well as altering the concentration of oxygen. In various regions of the tumor microenvironment, hypoxia, an essential player in the multistep phase of cancer metastasis, is necessary. Hypoxia can be turned into an advantage for selective cancer therapy because it is much more severe in tumors than in normal tissues. Cellular matrix gives signaling cues that control cell behavior and organize cells' elements in tissue development and homeostasis. The interplay between intrinsic factors of cancer cells themselves, including their genotype and signaling networks, and extrinsic factors of tumor stroma, for example, ECM and ECM remodeling, together decide the destiny and behavior of tumor cells. Tumor matrix encourages the development, endurance, and invasion of neoplastic and immune cell activities to drive metastasis and debilitate treatment. Incipient evidence recommends essential parts of tumor ECM segments and their remodeling in controlling each progression of the cancer-immunity cycle. Scientists have discovered that tumor matrix dynamics as well as matrix remodeling in perspective to anti-tumor immune reactions are especially important for matrix-based biomarkers recognition and followed by immunotherapy and targeting specific drugs.
Keywords: cancer-immunity cycle